OUTSOURCING IN EMPLOYMENT LAW REVIEWED BASED ON JUSTICE AND LEGAL CERTAINTY ASPECTS - Manurung, Mangaraja (UNISSULA, 2022)
Outsourcing is work with the PKWT systems, which are work agreements by companies that can support work at other companies. Before the enactment of the Job Creation Act, there were constraints on the activities of outsourced workers by not being able to do the main work for the company. After the Act's enactment, job creation did not have a job limit for outsourced workers. This study discusses how elements of justice and legal certainty in the law are discussed—employment regarding Outsourcing and How to Outsource after the enactment of the Job Creation Act. This study uses a statute approach to review all laws associated to the problems discussed. This research also applies a normative juridical research method under Indonesia's prevailing rules and regulations.